Aflibercept and navigated versus conventional laser in diabetic macular oedema: a 12‐month randomized clinical trial. Issue 4 (10th October 2019) - Blindbæk, Søren L.; Peto, Tunde; Grauslund, Jakob
Abstract: Purpose: To examine the efficacy of intravitreal aflibercept and navigated laser as compared to intravitreal aflibercept and conventional laser in diabetic macular oedema (DME) treatment. Methods: In 12‐month randomized clinical trial, 48 eyes of 37 patients with centre‐involved DME at Odense University Hospital were randomized 1:1 to receive three monthly injections of aflibercept followed by navigated (group A) or conventional (group B) focal/grid laser. From month four through twelve, patients were examined monthly, and additional injections were given pro re nata (PRN) (central retinal thickness [CRT]>20% from lowest measurement or loss in visual acuity [VA]>5 Early Treatment Diabetic Retinopathy Study [ETDRS] letters compared with baseline). Outcome measures; (1) percentage of eyes that needed additional injections after laser in group A and B, (2) mean number of injections in group A and B, and (3) mean change in VA and CRT in group A and B. Results: In the PRN phase, 60.5% of patients needed additional injections without differences between groups A and B (58.3 versus 63.2%, p > 0.99). The mean number of injections between baseline and month 12 was 4.4 (4.2 versus 4.6, p = 0.41). From baseline to month 12, VA improved by 8.4 ETDRS letters, and CRT was reduced by 97.4 μm (+9.4 versus +7.1 letters, p = 0.17, and −83.2 versus −115.4 μm, p = 0.21). Conclusion: No difference in need for retreatment was detected between treatment arms of aflibercept and navigated versus conventional laser.